Role of Artificial Intelligence in Enhancing Academic Performance of Undergraduate Business Students in Kathmandu Valley - B.C., Diksha (Nepalese Journal of Management, 2025)
This study examines the role of artificial intelligence in enhancing academic performance of undergraduate business students in Kathmandu valley. The dependent variable is student academic performance. The independent variables are attitude towards AI, access to resources, time saving, affordability, and ease of use. The study is based on primary data with 128 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing role of artificial intelligence in enhancing academic performance of undergraduate business students in Kathmandu valley. The study shows that attitude towards AI is positively correlated to student’s academic performance. It indicates that a better attitude toward AI leads to increase in student’s academic performance. Likewise, access to resources is positively correlated to student’s academic performance. It indicates that access to proper resources leads to increase in student’s academic performance. Similarly, time saving is positively correlated to student’s academic performance. It indicates that more time saved leads to enhancing student’s academic performance. Affordability is positively correlated to student’s academic performance. It indicates that higher affordability of AI tools leads to enhancement of students’ academic performance. Likewise, ease of use is positively correlated to student’s academic performance. It indicates that increase in use of AI leads to increase the enhancement of student’s academic performance.